Responses of Two Litter-Based Invertebrate Communities to Changes in Canopy Cover in a Forest Subject to Hurricanes - Richardson, Barbara; Richardson, Michael; González, Grizelle (Forests, 2018)
Tropical forests are subject to seasonal hurricanes resulting in cycles of canopy opening and deposition of litter, followed by periods of recovery and canopy closure. Herein, we review two studies of litter-based communities in Puerto Rico; (i) a survey of bromeliad invertebrates in three montane forest types along an elevational gradient in 1993–1997, during a period of canopy recovery after two severe hurricanes, and the results compared with those from a resurvey in 2010, and (ii) a large scale canopy trimming experiment in the lower montane (Tabonuco) forest designed to simulate an hurricane event, and to separate the effects of canopy opening from debris deposition. Measurements of changes in invertebrate community parameters and decay rates of litter were made in a litter bag experiment as part of this major experiment. As the canopy closed, during the periods of study, bromeliad density reduced, especially in the Tabonuco forest. This was associated with a decline in both alpha and gamma invertebrate diversity, which appears to have involved the loss of rarer species. In the Tabonuco forest, two endemic bromeliad specialists were not found during resampling in 2010, though the most common species were remarkably stable over the two decades. Canopy opening significantly altered the diversity, biomass, and composition of litter communities, irrespective of litter deposition. It particularly reduced organisms responsible for comminution of litter and increased the activity of fungivores and microbiovores. Both studies showed that canopy disturbance, either indirectly or directly, adversely affects invertebrate diversity and detrital processing.